Vers une analyse logico-linguistique des structures de comparaison - Amor tahar (OpenEdition, 2020)
In this paper, we are interested in the syntax of comparatives, and more particularly in the semantic analysis of sentence structures expressing the comparison. Comparatives, however, seem to be a very delicate field of research in syntactic analysis. The minimalist framework of generative grammar has proposed an analysis of the morphological traits specific to categories and their lexical realizations, which makes it possible to control the acceptability of structural configurations by syntax by referring to their semantic structures ; the objective of this study is to provide such an analysis and to allow a better understanding of the formation of comparative structures. By modeling comparisons in the form of predicate-argument pairs linked by semantic roles, we will try to present another semantic framework for representing the meaning of various natural language comparison constructs.